A novel lead-ion-imprinted magnetic biosorbent: preparation, optimization and characterization. Issue 4 (10th February 2019) - He, Yayuan; Xiao, Wen; Li, Guiyin; Yang, Fei; Wu, Pian; Yang, Tao; Chen, Cuimei; Ding, Ping
ABSTRACT: A novel biological material with high adsorption capacity and good selectivity for Pb 2+ was synthesized. Response surface methodology was utilized for the optimization of the variables during the synthesis. The synthesized biosorbent was characterized by scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FT-IR) and X-ray diffraction (XRD). The optimized preparation condition for lead-ion-imprinted magnetic biosorbent (Pb(II)-IMB) was obtained (0.19 g chitosan (CTS), 0.43 g magnetic Fe3 O4 and 2.11 mL/gCTS of epichlorohydrin). The highest value for the removal of lead ion was estimated to be 86.85%, with an absorption capacity of 69.48 mg/g. The characterization results indicated that Pb(II)-IMB was rich in adsorbable groups to adsorb metal ions. Because of the magnetic property of the synthesized products, it can be separated from the water easily. The relative selectivity coefficients of Pb(II)-IMB for Pb(II)/Cu(II), Pb(II)/Cd(II) and Pb(II)/Ni(II) were 2.32, 2.20 and 2.05 times higher than the non-imprinted magnetic biosorbent, respectively. Pb(II)-IMB could be reused at least five times with only ∼13% loss. These results suggested that Pb(II)-IMB was a new, efficient and low-cost material for removing Pb(II) from wastewater. GRAPHICAL ABSTRACT: UF0001